The Contribution of Rice Farming on The Farmers’ Income: a Study Case in Klambir V Kebun Village, Hamparan Perak Subdistrict, Deli Serdang Regency - Rizal P. Lubis; Abdiyanto; Sabilayana (Best Journal of Administration and Management, 2024)
Two objectives of agricultural expansion are food security and farmers’ welfare, thus the government must always endeavor to guarantee its availability through a range of policy initiatives. To improve farmers' income, it is also intended that the rice farming should be set at a level that generates a profit for farmers. The study was carried out in the Hamparan Perak District of the Deli Serdang Regency, specifically in Klambir V Kebun Village. This study's objective was to provide detailed information regarding the impact of rice farming on farmers' income. This study evaluated the literature using library research using a descriptive qualitative methodology. Information sources included field data pertinent to the topic as well as data from websites used as publication sources. The findings showed that 78.18% of farmers' household income came from rice cultivation, with side jobs outside of agriculture making up the remaining 21.82%. The rice growing method used in the current study is workable and can provide enough income to support a family. Rice farming has a significant impact on the welfare of the farmers.